2018
DOI: 10.1177/0194599818773070
|View full text |Cite
|
Sign up to set email alerts
|

Independent Predictors of Prognosis Based on Oral Cavity Squamous Cell Carcinoma Surgical Margins

Abstract: Objective To conduct a multivariate analysis of a large cohort of oral cavity squamous cell carcinoma (OCSCC) cases for independent predictors of local recurrence (LR) and overall survival (OS), with emphasis on the relationship between (1) prognosis and (2) main specimen permanent margins and intraoperative tumor bed frozen margins. Study Design Retrospective cohort study. Setting Tertiary academic head and neck cancer program. Subjects and Methods This study included 426 patients treated with OCSCC resection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 16 publications
1
32
0
2
Order By: Relevance
“…To address these issues, also two staging parameters, DOI and RM, which can be assessed during pathohistological examination of HE-slides, were evaluated separately. In concordance with other publications [43,47,48] resection margin could not be identified as a significant predictor of survival or LM, even when summarizing patients into subgroups (RM ≤ 1 mm, ≤ 5 mm, > 5 mm) according to values previously published as significant prognostic indicators [26,27]. These findings can possibly be explained with complete (R0) tumor resection being achieved in all patients of this collective and because mean RM was 6.0 mm and the number of patients with involved (RM ≤ 1 mm) margins was only 5.…”
Section: Resection Marginssupporting
confidence: 89%
See 1 more Smart Citation
“…To address these issues, also two staging parameters, DOI and RM, which can be assessed during pathohistological examination of HE-slides, were evaluated separately. In concordance with other publications [43,47,48] resection margin could not be identified as a significant predictor of survival or LM, even when summarizing patients into subgroups (RM ≤ 1 mm, ≤ 5 mm, > 5 mm) according to values previously published as significant prognostic indicators [26,27]. These findings can possibly be explained with complete (R0) tumor resection being achieved in all patients of this collective and because mean RM was 6.0 mm and the number of patients with involved (RM ≤ 1 mm) margins was only 5.…”
Section: Resection Marginssupporting
confidence: 89%
“…Resection margin (RM) on the other hand could not be identified as a significant predictor of OS or RFS. Patients were then summarized into subgroups (RM ≤ 1 mm, 1 mm < RM ≤ 5 mm, > 5 mm) according to values previously published as significant prognostic indicators [26,27], also yielding no significant result.…”
Section: Depth Of Invasion and Resection Marginmentioning
confidence: 99%
“…Two methods of IOARM can be distinguished: the traditional defect-driven IOARM based on frozen sections and the recently recommended specimen-driven assessment. Although the frozen section analysis is a well-known procedure available in many centers, studies have reported that it has no impact on regional control or an improvement in survival in OCSCC patients (Abbas, Ikram, Tariq, Raheem, & Saeed, 2017;Buchakjian et al, 2018;Buchakjian, Tasche, Robinson, Pagedar, & Sperry, 2016;Mair et al, 2017;Pathak et al, 2009;Varvares et al, 2015).…”
Section: How To Achie Ve " Fir S T Time Rig Ht " Surg Ery ?mentioning
confidence: 99%
“…In other reports, the main resection specimen alone defines the margin status and its prognostic value is not modified by re-excisions. 3,4 The College of American Pathologists offers some guidelines for Cancer November 1, 2018 margins revised into negative margins? In a randomized, single-blind, controlled trial, we recently compared 2 common methods of intraoperative resection margin assessment in patients with oral cavity squamous cell carcinoma.…”
Section: Patients With Revised Surgical Resection Margins Are Best Stmentioning
confidence: 99%
“…Recent articles have tried to approach this question, which was not assessed in our international study. [3][4][5][6][7] The main finding of these studies was that local control is reduced in patients with positive intraoperative frozen sections, despite the extension of surgery to obtain negative resection margins. Based on a previous prospective study performed at Rambam Health Care Campus, we estimate that the rate for this subgroup varies and is within the range of 10% to 30% depending on the method of resection margin assessment.…”
Section: Patients With Revised Surgical Resection Margins Are Best Stmentioning
confidence: 99%